Reflexiones para la construcción de política pública con impacto en el componente bucal de la salud - Ángela María Franco; Emilia Ochoa; Eliana Martínez (Universidad de Antioquia, 2004)
The workshop on Oral Health by the interinstitutional cooperation "Management of Public Policies and Health" has the objective of promoting a reflection conducive to the formulation of public health proposals that have a positive effect on the general health and its oral component. There are precedents of such policies and the local and international levels that have gone unrecognized by the reform to the social security system in health; this has produced, in the specific case of Medellin, the dismantling of public health programs that have proven their efficiency and efficacy in previous years. Some examples that show this statement are presented and some basic enunciates are proposed which should be part of a public policy with impact on the oral component of health. It concluded that the political, economic and demographic changes experienced by our country in the past recent years have given place to a determined profile of health disease which should be attended by the organized management of society. The oral component of health has also been affected and the dental practice called to respond to the new or old needs that the population has in this field.